THE INFLUENCE OF PRIMARY SERVICES AT THE COMMUNITY HEALTH CENTER, ONE OF WHICH IS THE ROLE OF NURSES IN PROVIDING COUNSELING IN THE FORM OF EDUCATION ABOUT ISPA AT THE KEDAI DURIAN COMMUNITY HEALTH CENTER MEDAN JOHOR DISTRICT IN 2024: THE INFLUENCE OF PRIMARY SERVICES AT THE COMMUNITY HEALTH CENTER, ONE OF WHICH IS THE ROLE OF NURSES IN PROVIDING COUNSELING IN THE FORM OF EDUCATION ABOUT ISPA AT THE KEDAI DURIAN COMMUNITY HEALTH CENTER MEDAN JOHOR DISTRICT IN 2024 - Gulo, Noferia; Lisdayanti Simanjuntak; Indra Agussamad; Rosmega; Petra Dian Sari Zega; Sanni Sihombing, (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
puskesmas plays a central role in driving health development with a focus on empowering families and communities, as well as being the primary health service provider at the first level. As part of the structure of the District/City Health Service, Puskesmas has responsibility for managing health development in its area. According to the World Health Organization (WHO), around 4.25 million deaths are caused by Acute Respiratory Infections (ISPA) every year throughout the world. In Indonesia, ISPA is consistently the main cause of death in infants and toddlers. ISPA data at the durian shop health center based on the total number of patients visiting from January-December 2023 reached 1928 and from the results of observations ISPA occurred due to air pollution, one of which was due to the presence of factories. ISPA can be transmitted through direct contact or droplets that are spread in the air when coughing or sneezing, and can infect other people through the eyes, mouth and nose. To reduce the incidence of ISPA at the Kedai Durian Community Health Center, the role of nurses is very important, one of which is carrying out several steps during field practice including preparing an Outreach Event Unit (SAP), making leaflets about ISPA, as well as presentations that educate the public about the definition of ISPA, causes, symptoms, risk factors. , prevention, and complications that may arise. These steps aim to increase public understanding of ISPA and encourage the adoption of effective prevention practices.